Pengaruh Profesionalisme Kerja Dan Semangat Kerja Terhadap Kinerja Pegawai Pada Puskesmas Sebarang Padang - Putri, Nadila Diana; Yanti, Novi; Yuliastanty, Susi (Fakultas Ekonomi, Universitas Ekasakti, 2024)
This research aims to determine the influence of work professionalism and work enthusiasm on the performance of Puskesmas Seberang Padang employees. Data collection methods are field research (Field Research) and library research (Library Research. Quantitative data type and data sources are primary data and secondary data. The population of this research is all employees of the Puskesmas across Padang. Sampling is done using a technique (non-probability). The data analysis method used is multiple linear regression analysis and coefficient of determination. Meanwhile, to test the hypothesis, the t test and f test are used. The results of the research are: (1) Work professionalism has a positive significant effect on the performance of the employees of the Puskesmas Seberang Padang. (2) Work Morale has a significant positive effect on employee performance in Puskesmas Seberang Padang. (3) Work professionalism and work enthusiasm have a significant positive effect together on employee performance in Puskesmas Seberang Padang.